Costs of Taxation and Benefits of Public Goods with Multiple Taxes and Goods - Anderson, James E. (2012)
The recent public economics literature involves an apparent consensus that income effects reduce the costs of raising revenues and hence increase the desirable level of public good provision. Higher taxes can indeed reduce the demand for leisure -- and hence increase the supply of taxed labor -- through income effects. However, the consensus is wrong because the income effects of taxes must be considered symmetrically with those from provision of public goods. This paper uses a model with multiple public goods and taxes to derive consistent measures of the marginal benefits of publicly-provided goods and their marginal social costs. With this model, the authors show that either compensated approaches excluding these income effects or uncompensated approaches including them may be used. If an uncompensated measure of the marginal cost of funds is used, however, the benefits of providing public goods should be adjusted with a simple, benefit multiplier not previously seen in the literature. Once this is done, the optimal level of public provision is independent of whether compensated or uncompensated approaches are used. Proper accounting for these income effects -- or their omission using a compensated approach -- appears to substantially raise the hurdle for government provision where there are substantial taxes bearing on labor.